A Sentimental Education - McGregor, Hannah (Wilfrid Laurier University Press, 2022)
How do you tell the story of a feminist education, when the work of feminism can never be perfected or completed? In A Sentimental Education, Hannah McGregor, the podcaster behind Witch, Please and Secret Feminist Agenda, explores what podcasting has taught her about doing feminist scholarship not as a methodology but as a way of life. Moving between memoir and theory, these essays consider the collective practices of feminist meaning-making in activities as varied as reading, critique, podcasting, and even mourning. In part this book is a memoir of one person's education as a reader and a thinker, and in part it is an analysis of some of the genres and aesthetic modes that have been sites of feminist meaning-making: the sentimental, the personal, the banal, and the relatable. Above all, it is a meditation on what it means to care deeply and to know that caring is both necessary and utterly insufficient. In the tradition of feminist autotheory, this collection works outward from the specificity of McGregor's embodied experience - as a white settler, a fat femme, and a motherless daughter. In so doing, it invites readers to reconsider the culture, media, political structures, and lived experiences that inform how we move through the world separately and together.Hannah McGregor has a very active Twitter and Instagram following Both Witch, Please (20,000 listeners +) and Secret Feminist Agenda have strong following. Witch, Please is a non-scholarly audience. SFA has a crossover audience topicality: TERFs and transphobic feminism; podcasting and its influence on feminism feminist scholars, gender and media scholars; life writing readers of Sara Ahmed or Donna Haraway Hannah is one of the co-authors of Refuse: CanLit in Ruins, which caused a buzz when it was released. models how to interweave personal writing and scholarship in media studies and literary criticism. How is scholarship transformed when we account for where we know from and how we relate to one another?